Family Financial Management during the Covid-19 Crisis: A Community Service Initiative for Tablanusu Village Jayapura Mothers - Labo, Irwan Adam; Ameliana, Yana; Kamaluddin, Santrio; Muhammad, Endang; Zein, Haris M (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Life is dynamic, twists and turns over a long period of time, many things can affect the financial goals that have been set, including during the current crisis due to the Covid-19 pandemic. We cannot close our eyes to the Covid-19 outbreak that occurred in the country of Indonesia at the beginning of 2020, causing a significant impact on almost all aspects of life. Not only health but also financial care is very important in solving this problem. However, good family financial management skills will help us get out of this problem easily. Through community service conducted by the teaching team and inviting students to discuss various solutions for family financial management for Tablanusu village mothers in times of crisis. The process of using this community service consists of the preparation stage starting from the inspection of the workplace, the work stage of introducing financial management, introducing finance, introducing household financial development with monitoring and analysis. The results obtained by the participants are equipping village mothers or PKK mothers with skills in managing family finances in times of crisis, so that they can help solve the problem of household arrangement funders in the future, such as ideas between partners and education costs. In organizing family finances, special solutions are needed, the use of money for certain purposes must be used as a measure of importance. Needs that are not urgent and only hobbies and activities that are not important can be crossed out of the list of expenses. Parents should make a list of basic/fundamental needs, secondary needs and advanced needs. Women PKK remove secondary and advanced requirements if they have not fulfilled all the basic requirements. There is an urgent need for household leaders to organize all essential needs, this work can empower housewives who were previously unfamiliar with family financial management. In the face of all the family financial management problems they face, they are consequently mothers who must be careful about spending too much money that has no result or value.